Sustainability Through Green Procurement: Interplay Between Leadership and Institutional Pressures - M., Waris; Ullah, Mehfooz; Lee, Chia Kuang (Future Academy, 2019)
Green Procurement is an emerging theme in the construction industry across the globe. However, construction firms often find it difficult to integrate sustainability performance indicators in construction projects especially in procurement. Literature shows that the construction industry has frequently encountered the disapproval of the regulatory authorities for neglecting or evading environmental regulations and it is particularly criticized for ignoring sustainability concerns in the procurement process. Therefore, in response to mounting institutional pressures, green procurement is emerging as a key strategic option for improving overall sustainability in construction industry. However, there is still much to be done as the research studies on green procurement identified that this strategy is not showing constant outcomes across the organizations owing to the organizational factors which impede or support in translating the green procurement strategy into practice at the organizational level. Therefore, through extensive review of the relevant literature, this study employs the theoretical lens of institutional theory in conjunction with transformational leadership to explore their role in enabling green procurement in construction firms. A hypothetical framework is thus proposed to analyse the role of transformational leadership in channelizing the institutional pressures for a pragmatic implementation of green procurement while effectively managing the inevitable change process at organizational level.